2012
DOI: 10.1002/cncr.27632
|View full text |Cite
|
Sign up to set email alerts
|

AMG 386 in combination with sorafenib in patients with metastatic clear cell carcinoma of the kidney

Abstract: BACKGROUND This study evaluated the tolerability and antitumor activity of AMG 386, a peptibody (a peptide Fc fusion) that neutralizes the interaction of angiopoietin-1 and angiopoietin-2 with Tie2 (tyrosine kinase with immunoglobulin-like and EGF-like domains 2), plus sorafenib in patients with clear cell metastatic renal cell carcinoma (mRCC) in a randomized controlled study. METHODS Previously untreated patients with mRCC were randomized 1:1:1 to receive sorafenib 400 mg orally twice daily plus intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 28 publications
(37 reference statements)
5
78
2
Order By: Relevance
“…In this study, toxicities were generally consistent with those that have been associated with monotherapy of trebananib, PLD, or topotecan [16,32,33]. Peripheral edema has been previously identified as a risk associated with trebananib treatment and generally manageable across studies [16,17,34,35]. Other AEs that have been associated with trebananib in combination with chemotherapy are ascites and pleural effusion [35].…”
Section: Discussionsupporting
confidence: 72%
“…In this study, toxicities were generally consistent with those that have been associated with monotherapy of trebananib, PLD, or topotecan [16,32,33]. Peripheral edema has been previously identified as a risk associated with trebananib treatment and generally manageable across studies [16,17,34,35]. Other AEs that have been associated with trebananib in combination with chemotherapy are ascites and pleural effusion [35].…”
Section: Discussionsupporting
confidence: 72%
“…The incidence and severity of edema (local and peripheral) observed in the present study (approximately half of patients and mostly mild) are commensurate with previous reports. Other adverse events associated with trebananib treatment are hypokalemia and pleural effusion [16,15,3], both of which also occurred in the present study, and ascites and proteinuria [15,19,16] which were not observed here.…”
Section: Discussioncontrasting
confidence: 65%
“…Inhibition of the angiopoietin pathway has been shown to result in tumor growth inhibition in preclinical models, with simultaneous inhibition of Ang1 and Ang2 resulting in greater tumor growth suppression compared with targeting either ligand in isolation (16,17). In early-phase clinical studies, treatment with trebananib (AMG 386), a peptibody that inhibits the interaction between Ang1 and Ang2 and the Tie2 receptor (18), showed anticancer activity, reducing tumor size and inducing objective responses in some patients (19)(20)(21)(22)(23). In a randomized, double-blind, phase III clinical study, trebananib plus weekly paclitaxel prolonged progression-free survival of patients with recurrent ovarian cancer compared with placebo plus paclitaxel [7.2 months vs. 5.4 months; HR, 0.66; 95% confidence interval (CI), 0.57-0.77; P < 0.0001; ref .…”
Section: Introductionmentioning
confidence: 99%